Quantum identity authentication scheme based on measurement-device-independent quantum key distribution protocol - Ying-di DONG; Jin-ye PENG; Xiao-bo ZHANG; Zhen-long ZHANG (Tongxin xuebao)
Utilized to security properties of measurement-device-independent quantum key distribution (MDI-QKD)protocol, quantum identity authentication scheme based on MDI (QIA-MDI)protocol was presented. In this protocol, authentication center (AC)and authentication user have encrypted authentication information and next authenticated key by shared key, and then they transmitted the encrypted information to untrusted third party for Bell-state measurement (BSM). The secret authentication information was obtained through the BSM result, which can verify the communicator identity and update shared key. The security performance of the proposed scheme is extensively analyzed and accordingly con?rmed in the case of attacks.